2000
DOI: 10.1002/(sici)1097-4636(200004)50:1<75::aid-jbm11>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Ligand accessibility as means to control cell response to bioactive bilayer membranes

Abstract: We report a new method to create a biofunctional surface in which the accessibility of a ligand is used as a means to influence the cell behavior. Supported bioactive bilayer membranes were created by Langmuir-Blodgett (LB) deposition of either a pure poly(ethylene glycol) (PEG) lipid, having PEG head groups of various lengths, or 50 mol % binary mixtures of a PEG lipid and a novel collagen-like peptide amphiphile on a hydrophobic surface. The peptide amphiphile contains a peptide synthetically lipidated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
112
2
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 32 publications
7
112
2
2
Order By: Relevance
“…Previous unsuccessful attempts to identify the bi-2H-azirin-2-yls 4. activities, [16] separation of membrane proteins by 2D electrophoresis, [17] creation of addressable arrays of modified lipid bilayer membranes for combinatorial chemistry, [18] and controlled cell culture on designed membrane surfaces. [19] Experimental Section Materials: Diacetylene lipid 1 and egg PC were purchased from Avanti Polar Lipids, Alabaster, AL, USA. NBD-PE (N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-1,2-dihexadecanoyl-sn-glycero-3-phosphoethanolamine) was purchased from Molecular Probes, Eugene, OR, USA.…”
contrasting
confidence: 82%
“…Previous unsuccessful attempts to identify the bi-2H-azirin-2-yls 4. activities, [16] separation of membrane proteins by 2D electrophoresis, [17] creation of addressable arrays of modified lipid bilayer membranes for combinatorial chemistry, [18] and controlled cell culture on designed membrane surfaces. [19] Experimental Section Materials: Diacetylene lipid 1 and egg PC were purchased from Avanti Polar Lipids, Alabaster, AL, USA. NBD-PE (N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-1,2-dihexadecanoyl-sn-glycero-3-phosphoethanolamine) was purchased from Molecular Probes, Eugene, OR, USA.…”
contrasting
confidence: 82%
“…The transfer of peptide-amphiphiles to hydrophobic surfaces and the subsequent effect of the surface on peptide conformation and orientation have been studied extensively. Atomic force microscopy shows the appropriate height "differential" for peptide-amphiphiles and lipids if peptide-amphiphiles are oriented upright (34,36). Neutron reflectivity data for triple helical peptideamphiphiles demonstrated that peptide head groups are oriented perpendicular to the air-water interface and retain the same conformation as in solution (36,45).…”
Section: Discussionmentioning
confidence: 99%
“…Atomic force microscopy shows the appropriate height "differential" for peptide-amphiphiles and lipids if peptide-amphiphiles are oriented upright (34,36). Neutron reflectivity data for triple helical peptideamphiphiles demonstrated that peptide head groups are oriented perpendicular to the air-water interface and retain the same conformation as in solution (36,45). In addition, peptideamphiphile orientation is nearly unaffected by changes in surface density (45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the formation of SLBs is simple 14 and they are highly resistant to nonspecific adsorption by proteins or cells. 12,[15][16][17][18] SLBs consist of a continuous lipid bilayer, 5 nm thick, separated from the substrate by a ϳ1 nm thin water cushion. Previous studies of cell adhesion with SLBs have relied on the use of lipids functionalized with peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of cell adhesion with SLBs have relied on the use of lipids functionalized with peptides. [18][19][20][21][22][23][24][25][26] The influence of the orientation, 20,22,23 accessibility, 18,26 a͒ Author to whom correspondence should be addressed. Electronic mail: a.brisson@iecb.u-bordeaux.fr conformation, 20,22 or mobility 27 of lipo-peptides on cell attachment and spreading have been characterized, thanks to the availability of a wealth of surface-sensitive techniques adapted to the SLB format.…”
Section: Introductionmentioning
confidence: 99%